Flow distortion into the core engine for an installed variable pitch fan in reverse thrust mode - Rajendran, David John; Pachidis, Vassilios (ASME, 2021)
The flow distortion at core engine entry for a Variable Pitch Fan (VPF) in reverse thrust mode is described from a realistic flowfield obtained using an integrated airframe-engine-VPF research model. 3D RANS solutions are generated for the complete aircraft landing run from 140 to 20 knots at different VPF settings. The internal reverse thrust flowfield is characterized by nozzle lip separation, pylon wake and recirculation of flow turned back from the VPF. A portion of the reverse flow turns 180° with separation at the splitter edge to feed the core engine. The core feed flow exhibits circumferential and radial non-uniformities that depend on the reverse flow development at different landing speeds. The temporal dependence of the distorted flow features is also explored by an URANS analysis. Total pressure and swirl angle distortion descriptors, and total pressure loss are described for the core feed flow at different VPF settings and landing speeds. It is observed that the radial intensity of total pressure distortion is critical to core engine operation, while the circumferential intensity is within acceptable limits. Therefore, the baseline sharp splitter edge is replaced by two larger rounded splitter edges of radii, ∼0.1x and ∼0.2x times the core duct height. This was found to reduce the radial intensity of total pressure distortion to acceptable levels. The description of the installed core feed flow distortion, as in this study, is necessary to ascertain stable core engine operation, which powers the VPF in reverse thrust mode.
Keywords: distortion; core engine operability; fluid dynamics and heat transfer phenomena in compressor and turbine components of gas turbine engines; Computational Fluid Dynamics (CFD); Compressor stall